PENGARUH MANAJEMEN KELAS DAN ETOS KERJA GURU TERHADAP EFEKTIVITAS PEMBELAJARAN DI SMP NEGERI 1 PAREPARE - Patmawati, Patmawati; Yunus, Muh.; Devilla, Rego; Yahya, Muh. (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
This study aims, (1) To analyze the effect of class management on the effectiveness of learning in SMP Negeri 1 Parepare, (2) To analyze the influence of teacher work ethic on the effectiveness of learning in SMP Negeri (3) To analyze the influence of classroom management and work ethic of teachers on effectiveness learning at SMP 1 Parepare. This research was conducted at SMP 1 Parepare with total teacher population is 85 teachers and students 954 Sampling technique that is purposive sampling technique, so that obtained sample 40 teachers and 150 students. In this study, the data obtained from the questionnaire. The results showed that 1) classroom management influenced the effectiveness of learning in SMP Negeri 1 Parepare. It is shown from the results of coefficients data titung class management is 2, 237 and t table = 2, 022. This indicates that thitung> ttable. It is also based on the sig value. for class management is 0,049 (p <0,05), (2) work ethic influence to effectiveness of learning at SMP Negeri 1 Parepare. It is proved by the result of regression test that the work ethic is 3.423 with t table = 2, 022. It shows that thitung> ttable. It is also based on the sig value. for work ethic variable value sig = 0,002 (p <0,05), (3) class management and work ethic influence to effectiveness of learning in SMP Negeri 1 Parepare. Based on the result of F test count equal to 83, 462 and sig value. F of 0.000 (<0.05).Â Key Words: Classroom Management, Working Ethics, Learning Effectiveness